Primordial Deuterium after LUNA: concordances and error budget. Issue 4 (8th April 2021) - Pisanti, O.; Mangano, G.; Miele, G.; Mazzella, P.
Abstract: The accurate evaluation of the nuclear reaction rates and corresponding uncertainties is an essential requisite for a precise determination of light nuclide primordial abundances. The recent measurement of the D(p, γ) 3 He radiative capture cross section by the LUNA collaboration, with its order 3% error, represents an important step in improving the theoretical prediction for Deuterium produced in the early universe. In view of this recent result, we present in this paper a full analysis of its abundance, which includes a new critical study of the impact of the other two main processes for Deuterium burning, namely the deuteron-deuteron transfer reactions, D(d, p) 3 H and D(d, n) 3 He. In particular, emphasis is given to the statistical method of analysis of experimental data, to a quantitative study of the theoretical uncertainties, and a comparison with similar studies presented in the recent literature. We then discuss the impact of our study on the concordance of the primordial nucleosynthesis stage with the Planck experiment results on the baryon density Ωb h 2 and the effective number of neutrino parameter Meff, as function of the assumed value of the 4 He mass fraction Yp . While after the LUNA results, the value of Deuterium is quite precisely fixed, and points to a value of the baryon density in excellent agreement with the Planck result, a combined analysis also including Helium leads to two possible scenarios with different predictions for Ωb h 2 and, depending on the value adopted for Yp from astrophysical measurements. We argue that new results on the systematics and mean value of Yp in metallicity poor environments would be of great importance in assessing the overall concordance of the standard cosmological model.